Effect of gestational protein restriction on left ventricle hypertrophy and heart angiotensin II signaling pathway in adult offspring rats - Silva, Renan Brisollada [UNESP]; Mesquita, Flávia Fernandes; Andreo, Marília [UNESP]; Assalin, Heloisa Balan [UNESP]; Gontijo, José Antônio Rocha; Boer, Patricia Aline [UNESP] (Scientific Research Publishing, 2013)
Maternal protein restriction may be a risk factor for cardiovascular disorders in adulthood. The RAS (renin-angiotensin-system) plays a pivotal role in cardiac remodeling. Components of the RAS, including angiotensin II (AngII) and its receptors type 1 (AT1R) and 2 (AT2R) are expressed in the heart. This study investigates whether gestational protein restriction alters the expression and localization of AT1R and AT2R and RAS signaling pathway proteins in parallel with left ventricle hypertrophy and systemic hypertension in male offspring. Dams were kept on normal (NP, 17% protein) or low (LP, 6% protein) protein diet during pregnancy. Systolic blood pressure (SBP) of male offspring was measured from the 8th to 16th week and left ventricles of 16-wk-old rats were processed for histology, morphometric, immunoblotting and immunohistochemistry. LP offspring showed a significant reduction in birth body weight and SBP increased significantly from the 8th week. Left ventricle mass and cardiomyocytes area were also significantly higher in LP animals. Widespread perivascular fibrosis was not detected in the heart tissue. Analysis by immunoblotting and immunohistochemistry demonstrated a significant enhance in cardiomyocyte expression of AT1R and ERK1 in LP offspring. Expression of PI3K in LP was significantly reduced in cardiomyocytes and in the intramural coronary wall, while AT2R expression was unchanged in the NP group. We also found reduced LP expression of JAK2 and STAT3. In conclusion, our data also suggest that changes in the RAS may play a role in the ventricular growth through upregulation of the AT1-mediated ERK1/2 response, despite unchanged AT2R expression.
Keywords: Low birth weight; Arterial hypertension; Fetal programming; Protein restriction; Angiotensin II; Left ventricle hypertrophy; Cardiovascular disease